The Principle of Profit Models - Lin, Guiping; Wei, Wei.; Zhu, Wuxiang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book mainly focuses on defining profit models, on how many main kinds of profit models there are, how profit models can change a company, and how to tailor a profit model to the needs of a certain company. In this context, profit models are classified as fixed-income, remaining-profit and profit-sharing, admission, toll, parking, fuel and sharing fees, profit sources, customer pricing, auction, combined pricing, etc. The logic behind all these profit models will be analyzed in detail and numerous micro-cases will be introduced. All of the micro-cases discussed are the best profit model practices used by outstanding enterprises, mainly from China and the USA (including HomeAway, Priceline, Tencent, Sina, Google, the Voice of China, CSPN and so on). These models will be complemented by a wealth of figures and additional tools to help readers better understand the principle of profit models. As such, the book not only explains (3z(Bwhy(3y (Bentrepreneurs preferred to apply a specific kind of profit model and not others, but also answers (3z(Bhow(3y (Bthey derived that model.s
Profit sources (Stakeholders). -Fixed income -- Remaining profit -- Profit sharing -- Customer pricing -- Auction -- Combined pricing.
Keywords: Economics; Industrial management; Entrepreneurship; Economics/Management Science; Economic Theory; Entrepreneurship; Management/Business for Professionals